2018
DOI: 10.1111/jpn.12937
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of surfactin production from Bacillus subtilis in fermentation and its effects on Clostridium perfringens‐induced necrotic enteritis and growth performance in broilers

Abstract: Bacillus species are commonly used as probiotics in the poultry feed industry for preventing infectious diseases and improving productivity by altering gastrointestinal microbiota. The growth parameters of Bacillus subtilis for surfactin production in fermentation and the benefits of surfactin on broiler chickens remain unclear. In this study, we examined the growth parameters of B. subtilis in fermentation and evaluated the effects of surfactin from B. subtilis-fermented products on Clostridium perfringens-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
(44 reference statements)
1
39
0
2
Order By: Relevance
“…Many studies have reported that dietary supplementation of Bacillus subtilis can prevent NE in broiler chickens by competitive exclusion of Clostridium perfringens in the gastrointestinal tract (La Ragione and Woodward, 2003;Tactacan et al, 2013;Jayaraman et al, 2013;Cheng et al, 2018). It has been shown that Bacillus licheniformis isolated from broiler gastrointestinal tract reveals antimicrobial activity against a broad spectrum of pathogens, such as Clostridium perfringens in vitro (Barbosa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that dietary supplementation of Bacillus subtilis can prevent NE in broiler chickens by competitive exclusion of Clostridium perfringens in the gastrointestinal tract (La Ragione and Woodward, 2003;Tactacan et al, 2013;Jayaraman et al, 2013;Cheng et al, 2018). It has been shown that Bacillus licheniformis isolated from broiler gastrointestinal tract reveals antimicrobial activity against a broad spectrum of pathogens, such as Clostridium perfringens in vitro (Barbosa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternative strategies to prevent NE in broilers are needed in the poultry industry. Over the past few years, it has been demonstrated that dietary supplementation of probiotics can inhibit the growth of gastrointestinal pathogens and subsequent diseases by producing antimicrobial substances (Patterson and Burkholder, 2003;Lutful Kabir, 2009;Cheng et al, 2018). Among Bacillus species, Bacillus licheniformis has been Optimization of solid-state fermentation conditions of Bacillus licheniformis and its effects on... Lin et al identified in the gastrointestinal tract of broilers with activity against Clostridium perfringens in vitro (Barbosa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several antibiotic alternatives have been proposed for prophylactic treatment of diseases, such as probiotics (Abudabos et al 2013, 2017; Cheng et al 2018, 2019). In recent years, fermented products produced from Bacillus subtilis and Bacillus licheniformis have gained attention as probiotic supplements in animal feed due to the production of thermostable and low pH resistant spores (Cheng et al 2018; Lin et al 2019). B. subtilis and B. licheniformis have been identified from the gastrointestinal tract of broilers with antimicrobial activity (Barbosa et al 2005; Cheng et al 2018; Lin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics have garnered interest as the alternative to AGP [6][7][8][9]. Probiotics can inhibit the growth of enteric pathogens and the development of subsequent diseases by producing antimicrobial substances in livestock [10][11][12][13]. A recent study reported that Lactobacillus species and Clostridium butyricum-fermented products alleviate diarrhea incidence and reduce the gut pathogens in weaning piglets [14].…”
Section: Introductionmentioning
confidence: 99%